2017
DOI: 10.1146/annurev-marine-122414-033819
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Anchovy, and Sardine

Abstract: Anchovy and sardine populated productive ocean regions over hundreds of thousands of years under a naturally varying climate, and are now subject to climate change of equal or greater magnitude occurring over decades to centuries. We hypothesize that anchovy and sardine populations are limited in size by the supply of nitrogen from outside their habitats originating from upwelling, mixing, and rivers. Projections of the responses of anchovy and sardine to climate change rely on a range of model types and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
153
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 140 publications
7
153
1
2
Order By: Relevance
“…One of the major topics about sardine stock is about a climate change behind the synchronous stock variation of sardines (e.g., Chavez, Ryan, Lluch‐Cota, & Niquen, ). Ecological characteristics of sardine are mainly compared with anchovy in the context of the species replacement (e.g., Checkley, Asch, & Rykaczewski, ). However, the difference of ecological characteristics between sardines will be also interesting to study in order to understand the sardine stock variation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major topics about sardine stock is about a climate change behind the synchronous stock variation of sardines (e.g., Chavez, Ryan, Lluch‐Cota, & Niquen, ). Ecological characteristics of sardine are mainly compared with anchovy in the context of the species replacement (e.g., Checkley, Asch, & Rykaczewski, ). However, the difference of ecological characteristics between sardines will be also interesting to study in order to understand the sardine stock variation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the spawning grounds of small pelagic fishes are known to expand or contract following changes in abundance of the reproductive stock (Checkley, Jr, Alheit, Oozeki, & Roy, ; Giannoulaki et al, ; Saraux et al, ). The populations of small pelagics are naturally subject to strong abundance fluctuations (Checkley, Asch, & Rykaczewski, ) which may be more pronounced in those species under heavy fisheries exploitation, where age class structure is usually truncated with very low individuals in age classes beyond 1‐ or 2‐year‐olds. Changes in the location and extent of spawning habitat for species of commercial interest have received a lot of research attention (inter alia, Brosset et al, ; Giannoulaki et al, ; Saraux et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated clear top‐down fishing effects on forage fish, usually exemplified by the dramatic collapses of commercially important small pelagic fish stocks of herring, sardines and anchovies (e.g., Coetzee, van der Lingen, Hutchings, & Fairweather, ; Dragesund, Hamre, & Ulltang, ; Fréon, Bouchon, Mullon, García, & Ñiquen, ). In addition, bottom‐up forcing, mediated through direct physiological responses to environmental factors or indirect responses to climate‐driven changes in the composition and availability of zooplankton prey has been shown to underlie large‐scale fluctuations of forage fish, such as the alternating dominance of sardines and anchovies in upwelling systems (Baumgartner et al., ; Schwartzlose et al., ; Alheit & Niquen, ; Van der Lingen, Hutchings, & Field, ; Checkley, Asch, & Rykaczewski, ). Although many studies have identified single drivers, the potential synergy of multiple internal and external factors in regulating population dynamics of forage fish, as well as their relative importance throughout ontogeny is a largely unresolved issue (Hjermann, Ottersen, & Stenseth, ; Lindegren & Checkley, ; Lindegren, Östman, & Gårdmark, ).…”
Section: Introductionmentioning
confidence: 99%